Little girls - Van Lente, Fred (Wolverine. First class., 2010)
While Professor X, Dr. MacTagert, Banshee, and others go out to dinner, Logan stays home to watch the seventh game of the Stanley Cup finals and look after Piotr's sister, Illyana. Kitty Pryde, Siryn, and Amp agree to keep Illyana entertained. The girls explore the basement and run a training program involving robot replicas of evil mutants. They soon become bored with the program, leaving it running while they play a game of "Spin the Secrets," leading to an unwelcome interruption of Logan's plans.